PENGEMBANGAN BAHAN AJAR BERBASIS CDL (CONTEXTUAL DIGITAL LITERACY) PADA MATERI JUAL BELI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN BULUSARI 3 - Aswin Fahrul Hidayat; Erwin Putera Permana; Agus Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the results of observations at SDN Bulusari 3 class IV in the subject of Science, the material of buying and selling activities which showed that class IV students still had difficulty understanding the material as evidenced by the average student score of 43. One of the causes is that teachers tend to use teaching materials that are less varied, resulting in students being less enthusiastic in participating in learning. To overcome this problem, it is necessary to develop innovative teaching materials in accordance with the material. This study aims to 1) determine the validity, 2) practicality, and 3) effectiveness of digital literacy teaching materials. The method used is the R&D (Research and Development) method with the ADDIE development model. Data collected through a validation questionnaire of teaching materials and materials, student response questionnaires, and pretests and posttests carried out by students. Through the results of the validation of teaching materials and materials experts, a percentage of 86% and 89% were obtained, which can be said that the teaching materials are valid. Furthermore, in the provision of student response questionnaires, a percentage score of 90% was obtained, stating that the teaching materials are practical to use. In the pretest that students completed, the average score was 54. Meanwhile, in the posttest that students completed, the average score was 80. Based on the results of the pretest and posttest, the digital literacy teaching materials can be said to be effective and can improve learning outcomes.